The Effect of The Combination of Slow Deep Breathing and Humming on Improving Oxygen Saturation of Inpatients With Pneumonia at RSUD Jayapura - Jufuwai, Susana; Prabawati, Dewi; Tjitra, Emiliana (Journal of Nursing Science Update (JNSU), 2023)
Pneumonia is an infectious disease affecting the lower respiratory tract with signs and symptoms such as coughing and shortness of breath. Pneumonia cases in Indonesia are estimated to have 4 million deaths due to pneumonia every year. This study aims to analyze the effectiveness of Slow, Deep Breathing and Humming techniques on changes in oxygen saturation in pneumonia patients at Jayapura Regional Hospital. This quantitative research uses a quasi-experimental pre-test and post-test approach without a control group design. The sample consisted of 30 subjects who were given a slow deep breathing technique intervention of 5 cycles in 15 minutes and humming four cycles in 10 minutes, done once daily for six days. The instruments in the research used the Pulse Oximetry tool. The sampling technique used nonprobability sampling with total sampling. The results showed a difference in SpO2 values before and after the Slow, Deep Breathing, and Humming intervention was carried out in subjects with pneumonia with a p= 0.001 (p < 0.05). It can be interpreted that the Hypothesis (Ha1) is accepted so that it can be concluded that the slow, deep breathing and humming interventions can help improve Sp02. There is a need for further research on nurses' complementary therapy in oxygenation management, where this exercise is one of the nurse's interventions in overcoming decreased SpO2 in pneumonia patients.